Factors Associated for Anti Tuberculosis Treatment Non-Adherence Among Tuberculosis Patients: Scoping Review - Zumardi Agus; Purnawan Junadi; Rosmala Atina Rusadi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Tuberculosis (TB) is one of the leading causes of death in the world. Every year more than 10 million people continue to be infected with TB. One of the main challenges in controlling TB is patient non-compliance in taking medication. This causes TB treatment failure, drug resistance, high mortality rates, and prolonged transmission of TB in the community. Objective: This article aims to describe the factors associated for anti tuberculosis treatment amongTB patients. Method: This study uses a literature review from 2021-2024 on four databases, namely Scopus, ProQuest, ScienceDirect, PubMed using the keywords factors associated, non-adherence, anti-tuberculosis treatment. The results of the screening obtained 111 articles and after selection, 5 articles were obtained that met the criteria for the purpose of writing. Result: The review results found that lack of family support (OR = 3.51, 95% CI: 1.15, 10.75), socio-demographic status male (OR = 1.41, 95% CI: 1.18, 1.68), older age (OR = 1.56, 95% CI: 1.05, 1.67), lower education (OR = 1.60, 95% CI: 1.27, 2.03) , drug side effect (OR = 2.3, 95% CI: 1.1, 4.9) , smoking status (OR = 1.78, 95% CI: 1.47, 2.16) assosiated for non-adherence anti tuberculosis treatment among TB pastients. Conclusion: Factors such as lack of family support, demographic status (male and older age), lower education, drug side effects, smoking status affect non-adherence to medication in TB patients. Interventions targeting the importance of family support, campaigns targeting older age, males and smokers need to be conducted to increase knowledge about TB, as well as increasing counseling on drug side effects and emphasizing the importance of medication adherence when providing counseling to TB patients.